Further studies on the reliability of the bacitracin inhibition test for the presumptive identification of Lancefield group A streptococci. - Coleman, D J (1977)
The reliability of the bacitracin inhibition test to differentiate between 125 Lancefield group A and 122 non-group A beta-haemolytic streptococci was studied. Bacitracin discs containing 0-02, 0-04, or 0-1 international units and the conditions recommended by both the Association of Clinical Pathologists and the Federal Drug Administration for routine sensitivity testing were used. The results suggest that the presence or absence of a zone of inhibition around a 0-04 unit disc can be used routinely for the presumptive identification of group A streptococci and that a specific zone size can be used for reading the test only with a 0-1 unit disc.